2019
DOI: 10.1136/bmjgh-2018-001319
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy and disparities in survival among HIV-infected people receiving antiretroviral therapy: an observational cohort study in Kathmandu, Nepal

Abstract: IntroductionThe advent of antiretroviral therapy (ART) has dramatically slowed down the progression of HIV. This study assesses the disparities in survival, life expectancy and determinants of survival among HIV-infected people receiving ART.MethodsUsing data from one of Nepal’s largest population-based retrospective cohort studies (in Kathmandu, Nepal), we followed a total of 3191 HIV-infected people aged 15 years and older who received ART over the period of 2004–2015. We created abridged life tables with ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…Delayed presentation and impaired functional status are additional factors that impact long-term prognosis following critical illness in these settings. Notwithstanding these challenges, emerging evidence suggests similar and improving trends to those observed in developed settings [102,103].…”
Section: Long-term Outcomes Following Critical Illnessmentioning
confidence: 92%
“…Delayed presentation and impaired functional status are additional factors that impact long-term prognosis following critical illness in these settings. Notwithstanding these challenges, emerging evidence suggests similar and improving trends to those observed in developed settings [102,103].…”
Section: Long-term Outcomes Following Critical Illnessmentioning
confidence: 92%
“…Nevertheless, major strides have been made on multiple fronts, and HIV infection has become a manageable chronic condition, especially due to the advent of very potent antiretroviral drugs [ 2 ]. As a matter of fact, despite disparities in survival rates across population groups and geographical settings, the expected life span of an HIV-infected person has increased remarkably following the introduction of antiretroviral treatment (ART), being almost equal to that of a non-infected person of the same age [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The global roll-out of effective antiretroviral treatment (ART) regimens for people living with HIV (PLWH) has significantly improved life expectancy [ 1 , 2 ]. As this population ages, it has been observed that other comorbidities such as cerebrovascular disease (CVD) are seen with greater frequency than in the general population [ 3 , 4 ••, 5 , 6 , 7 ••].…”
Section: Introductionmentioning
confidence: 99%